2005
DOI: 10.1161/01.res.0000155331.09458.a7
|View full text |Cite
|
Sign up to set email alerts
|

A Defect of Neuronal Nitric Oxide Synthase Increases Xanthine Oxidase-Derived Superoxide Anion and Attenuates the Control of Myocardial Oxygen Consumption by Nitric Oxide Derived From Endothelial Nitric Oxide Synthase

Abstract: Abstract-Endothelial nitric oxide synthase (eNOS) plays an important role in the control of myocardial oxygen consumption (MVO 2 ) by nitric oxide (NO). A NOS isoform is present in cardiac mitochondria and it is derived from neuronal NOS (nNOS). However, the role of nNOS in the control of MVO 2 remains unknown. MVO 2 in left ventricular tissues from nNOS Ϫ/Ϫ mice was measured in vitro. Stimulation of NO production by bradykinin or carbachol induced a significant reduction in MVO 2 in wild-type (WT) mice. In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
62
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 43 publications
7
62
1
Order By: Relevance
“…Importantly, the increased level of XOR activity in ob/ob mice is independent of XOR abundance, since proteins levels are similar in WT and ob/ob mice. This phenomenon is in accordance with previous findings from our group [33] and others [34] that have shown higher XOR activity in NOS1 −/− mice resulting in higher ROS production despite unchanged levels of XOR protein abundance. The increase in oxidative stress in ob/ob mice was not related to NADPH oxidase, which is another important source of ROS in the heart [23], as the expression of its subunits was similar between ob/ob mice and controls.…”
Section: Discussionsupporting
confidence: 94%
“…Importantly, the increased level of XOR activity in ob/ob mice is independent of XOR abundance, since proteins levels are similar in WT and ob/ob mice. This phenomenon is in accordance with previous findings from our group [33] and others [34] that have shown higher XOR activity in NOS1 −/− mice resulting in higher ROS production despite unchanged levels of XOR protein abundance. The increase in oxidative stress in ob/ob mice was not related to NADPH oxidase, which is another important source of ROS in the heart [23], as the expression of its subunits was similar between ob/ob mice and controls.…”
Section: Discussionsupporting
confidence: 94%
“…1,2 In addition, NOS1 constrains the activity of cardiac xanthine oxidoreductase (XOR), a major source of O 2 ⅐Ϫ in the heart, with which it forms a protein-protein interaction. 3,4 This in turn contributes to maintaining tissue balance between the production of reactive nitrogen species (RNS) and reactive oxygen species (ROS), the nitroso-redox balance. [3][4][5][6] After myocardial infarction (MI) and in failing myocardium due to dilated cardiomyopathy, NOS1 alters its subcellular localization and translocates to the sarcolemma, 7,8 where it exerts an inhibitory effect on ␤-adrenergic activity.…”
mentioning
confidence: 99%
“…3,4 This in turn contributes to maintaining tissue balance between the production of reactive nitrogen species (RNS) and reactive oxygen species (ROS), the nitroso-redox balance. [3][4][5][6] After myocardial infarction (MI) and in failing myocardium due to dilated cardiomyopathy, NOS1 alters its subcellular localization and translocates to the sarcolemma, 7,8 where it exerts an inhibitory effect on ␤-adrenergic activity. The latter has been theorized to be maladaptive and a contributor to left ventricular (LV) dysfunction.…”
mentioning
confidence: 99%
“…nNOS suppresses the activity of the cardiac XOR, which is one of the major sources of O 2 Ϫ production in the heart. It has been shown that this targeted inhibition maintains the balance between the production of reactive nitrogen species and reactive oxygen species (ROS) 3,8,9 in cardiac tissues. nNOS, also found in mitochondria, 10,11 inhibits the mitochondrial respiratory chain, resulting in inhibition of ATP production.…”
mentioning
confidence: 99%